2021
DOI: 10.1088/1361-6579/ac19f9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ambulatory monitoring devices to measure energy expenditure and heart rate in a military setting

Abstract: Objectives.To investigate the validity of different devices and algorithms used in military organizations worldwide to assess physical activity energy expenditure (PAEE) and heart rate (HR) among soldiers. Design. Device validation study. Methods. Twenty-three male participants serving their mandatory military service accomplished, firstly, nine different military specific activities indoors, and secondly, a normal military routine outdoors. Participants wore simultaneously an ActiHeart, Everion, MetaMax 3B, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The heart rate is determined by the ECG recorded by the electrodes embedded in the chest belt, which allows the accurate determination of heart rate the same as clinical evaluations [ 23 , 24 , 25 ]. A possible disadvantage of the chest-belt-type wearable is that it has been known to be a discomfort due to the wrapping around the chest [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The heart rate is determined by the ECG recorded by the electrodes embedded in the chest belt, which allows the accurate determination of heart rate the same as clinical evaluations [ 23 , 24 , 25 ]. A possible disadvantage of the chest-belt-type wearable is that it has been known to be a discomfort due to the wrapping around the chest [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that when measuring HR, using a HR monitor based on ECG technology is preferred over the internal PPG (Castaneda et al, 2018) measurement method located in the clock itself (Ge et al, 2016;Gillinov et al, 2017;Etiwy et al, 2019;Baek, Ha and Park, 2021). HR was measured using the Garmin HRM-Pro belt, and a similar setup has earlier proven to be highly accurate (Gilgen-Ammann et al, 2021). Combining the fact that the positioning system is relatively accurate, that it is possible to obtain HR measurements, and that all data (i.e., position, distance traveled, and HR) is extracted at the same timestamp makes this measuring system a suitable candidate for easy measuring sports equipment performance.…”
Section: Experiments Designmentioning
confidence: 99%
“…PPG detects the pulse rate, corresponding to heart rate, which can be detected from the R wave on an electrocardiogram (ECG). In addition, shirt-type or belt-type and other textile based sensors equipped with ECG measurement electrodes that can be placed in close contact with the chest or other parts of the surface body are also widespread [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For heart rate measurement, PPG-type sensors detect pulse rates from blood flow changes in the vicinity of the measurement area.…”
Section: Introductionmentioning
confidence: 99%